Histone H2A.z Is Essential for Cardiac Myocyte Hypertrophy but Opposed by Silent Information Regulator 2α - Ieng-Yi Chen; Jacqueline Lypowy; Jayashree Pain; Danish Sayed; Stan Grinberg; Ralph R. Alcendor; Junichi Sadoshima; Maha Abdellatif (2006)
In this study we have shown that the histone variant H2A.z is up-regulated during cardiac hypertrophy. Upon its knock-down with RNA interference, hypertrophy and the underlying increase in growth-related genes, protein synthesis, and cell size were down-regulated. During attempts to understand the mode of regulation of H2A.z, we found that overexpression of silent information regulator 2alpha (Sir2alpha) specifically induced down-regulation of H2A.z via NAD-dependent activity. This effect was reversed by the proteasome inhibitor epoxomicin, suggesting a Sir2alpha-mediated ubiquitin/proteasome-dependent mechanism for degradation of H2A.z. An increase in Sir2alpha also resulted in a dose-dependent reduction of the response to hypertrophic stimuli, whereas its inhibition resulted in enhanced hypertrophy and apoptosis. We have shown that Sir2alpha directly deacetylates H2A.z. Mutagenesis proved that lysines 4, 7, 11, and 13 do not play a role in the stability of H2A.z, whereas Lys-15 was indispensable. Meanwhile, Lys-115 and conserved, ubiquitinatable Lys-121 are critical for Sir2alpha-mediated degradation. Fusion of the C terminus of H2A.z (amino acids 115-127) to H2A.x or green fluorescence protein conferred Sir2alpha-inducible degradation to the former protein only. Because H2A.x and H2A.z have conserved N-tails, this implied that both the C and N termini are critical for mediating the effect of Sir2alpha. In short, the results suggest that H2A.z is required for cardiac hypertrophy, where its stability and the extent of cell growth and apoptosis are moderated by Sir2alpha. We also propose that Sir2alpha is involved in deacetylation of H2A.z, which results in ubiquitination of Lys-115 and Lys-121 and its degradation via a ubiquitin/proteasome-dependent pathway.